Effect of Er2O3dopant on electrical and optical properties of potassium sodium niobate silicate glass-ceramics - Ploypailin Yongsiri (2018)
© 2015 Elsevier Ltd. All rights reserved. In this study, transparent glass-ceramics from potassium sodium niobate (KNN)-silicate glass system doped with erbium oxide (Er 2 O 3 ) were successfully prepared by incorporation method. KNN was added in glass batches as heterogeneous nucleating agent. The KNN powder was mixed with SiO 2 and Er 2 O 3 dopant with KNN and Er 2 O 3 content varied between 70-80 and 0.5-1.0 mol%, respectively. Each batch was subsequently melted at 1300°C for 15 min in a platinum crucible using an electric furnace. The quenched glasses were then subjected to heat treatment at various temperatures for 4 h. XRD results showed that the prepared glass ceramics contained crystals of KNN solid solution. In contrary, dielectric constant (ε r ) and dielectric loss (tan δ) were found to increase with increasing heat treatment temperature. Additionally, optical properties such as absorbance and energy band gap have been investigated.